TRANSFORMASI PRAKTIK PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI TADIKA MALAYSIA - Jessica May Ritonga; Hasrian Rudi Setiawan (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Islamic Religious Education (IRE) plays a fundamental role in shaping students’ religious character from an early age. At the preschool level, particularly in tadika institutions, Islamic Religious Education is not merely oriented toward the transmission of religious knowledge, but also toward the internalization of Islamic values through habituation, role modeling, and meaningful learning experiences. Along with the development of educational paradigms, the practice of Islamic Religious Education in early childhood education has undergone significant transformation toward more humanistic, contextual, and learner- centered approaches. This study aims to examine the transformation of Islamic Religious Education practices in shaping the religious character of students in Malaysian tadika. The study focuses on teaching strategies, learning methods, and the role of teachers in implementing Islamic Religious Education oriented toward character formation. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation conducted continuously within the tadika setting. The sources of data include teachers, students, school management, and supporting learning documents. The findings of this study are expected to provide an in-depth understanding of how Islamic Religious Education practices are transformed in early childhood education and how these practices contribute to the formation of students’ religious character. This research is expected to contribute theoretically to the development of Islamic Religious Education studies and practically to teachers and educational institutions in designing more effective, contextual, and developmentally appropriate Islamic Religious Education practices at the preschool level.